The Effect of Recycled Crushed Brick Aggregate on the Physical–Mechanical Properties of Earth Blocks - Carlos Alberto Casapino-Espinoza; José Manuel Gómez-Soberón; María Consolación Gómez-Soberón (Buildings)
The use of different components, such as alternative aggregates, represents an innovation in construction. According to various studies, these components improve certain properties of the elements that incorporate them. Specifically, recycled construction aggregates (RCAs)—such as crushed ceramic bricks (CCBs)—offer several benefits, including reducing landfill waste, enhancing the mechanical properties of the elements that integrate them, and ensuring availability. This research focuses on utilizing these waste materials and determining their feasibility and compatibility (in the short term) for manufacturing traditional earth blocks (EBs). This is achieved by studying the physical and mechanical properties of CCBs in matrices for EB construction, adhering to performance standards, emphasizing the advantages these aggregates provide for mechanical properties in sustainable construction and applying them in the context of traditional construction. Correlations were established through a statistical study of experimental data, graphically indicating the relationship between the different properties of CCBs, the mix design process, and the structural behavior of the resulting EB. Based on the key variable of the CCB replacement percentage, properties such as the elastic module by ultrasound, porosity, and expansion by hygroscopicity were analyzed, alongside mechanical properties like compressive and flexural strength. The results show that EBs with CCBs increases porosity by up to 21.59%. These blocks exhibit dimensional shrinkage of up to 14.5%, correlating with the increase in the CCB content. This aggregate replacement leads to a reduction in compressive strength (up to −23%) and flexural strength (up to −17.43%); however, all CCB content levels studied met the requirements of the applied standards. It is concluded that CCBs satisfactorily modifies the properties of the EBs and is suitable for use in construction.